La sociologie du travail en Espagne : l’urgence d’un retour aux débats fondateurs - Alberto Riesco-Sanz; Pilar Carrasquer Oto (La Nouvelle Revue du Travail)
The sociology of work is a well-established field of research within Spanish sociology. Having achieved a certain level of institutionalisation, the discipline’s main research topics have started to diverse and evolve in sync with the transformations witnessed in Spanish society. Criticism of traditional approaches has also led to a redefinition, with the analytical framework now incorporating debates such as gender and/or employment-based inequality. Even as certain continuities remain, in Spain the sociology of work has come to be characterised by an at least partial move towards a variant of sociology that is more empirical, interdisciplinary, methodologically heterogenous and focused on international comparisons – and less embedded in so-called local problems. In addition, it is a somewhat disoriented and even ephemeral kind of sociology, hence one that is apt to revive a number of seminal debates, starting with the apprehension of its own object of study.